Pragmatisme Politik di Indonesia: Kandidat, Koalisi Partai Politik dan Calon Tunggal dalam Pemilihan Kepala Daerah: Candidates, the Coalition of Political Parties and Single Candidate for Local Elections - Rosanti, Ratna (Research and Development Agency Ministry of Home Affairs, 2020)
Political pragmatics has become its dynamic in Local Elections. The existence of incumbent power and uneven coalition formation of parties in the election can directly reduce or eliminate the opportunity for other political parties to participate in the election. In addition to these problems, so far, candidates' nomination by political parties turns out to pay more attention to the incumbent electability or popularity of the candidates to be carried by them and without assuming to party ideology. This certainly makes the power imbalance so that candidates from political parties or coalitions of other political parties are reluctant to compete. Political parties hold a coalition to carry out the candidates for various reasons. This research article will explain political parties' pragmatics in forming a coalition and carrying a pair of candidates that gave rise to a single candidate's phenomenon. The research article begins with collecting data through a literature study and is supported by the General Elections Commission's data. To answer this phenomenon, the writer analyzes the documentation as long as the Local Elections is held simultaneously. The concept of political pragmatism is expected to explain these phenomena. This paper concludes that the pragmatic methods used by political parties in determining coalitions and candidates in the Regional Head Election are because the purpose of political parties to participate in the contestation is only a victory to gain power.